2013
DOI: 10.3892/or.2013.2659
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor enhances the activity of invasion and metastasis in thyroid cancer cells

Abstract: Thyroid cancer sometimes contains poorly differentiated components, which have the potential of invasion and metastasis. We evaluated the possible roles of heparin-binding EGF-like growth factor (HB-EGF), a member of the epidermal growth factor (EGF) family, in cell growth and invasion of thyroid cancer cells, and demonstrated that HB-EGF is not only a potent mitogen but also a chemotactic factor in the thyroid cancer cells 8305C and SW579. The HB-EGF-mediated chemotaxis was inhibited by neutralizing antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…20 HBEGF, a mitogen and a potent chemotactic factor, mediates the invasion and metastasis of PTC. 10 PLGF plays critical roles in the pathologic angiogenesis of PTC through regulating matrix metalloproteinases. 11 PDGF-BB, recognized as the most potent lymphangiogenic factor, can bind with high affinity to PDGF receptor-a to promote lymphatic metastases in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…20 HBEGF, a mitogen and a potent chemotactic factor, mediates the invasion and metastasis of PTC. 10 PLGF plays critical roles in the pathologic angiogenesis of PTC through regulating matrix metalloproteinases. 11 PDGF-BB, recognized as the most potent lymphangiogenic factor, can bind with high affinity to PDGF receptor-a to promote lymphatic metastases in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 HBEGF may be a key gene linking uterine overdistention with preterm labor, inflammation, and myometrial tissue remodeling; HBEGF has been identified as up-regulated in stretch of the human bladder, 69 spontaneous labor at term, 70 cell migration and tissue remodeling, 71,72 and as a chemotactic factor in cancer cells. 73 Up-regulation of TGFBI also acts to inhibit cell adhesions, thereby increasing cell motility. 74 Additional evidence for tissue remodeling came from the identification by IPA of activated canonical pathways (HMGB1, calpain proteases) and transcription factors (hepatocyte growth factor) classically associated with cell migration.…”
Section: Commentmentioning
confidence: 99%
“…However, it can sometimes be aggressive, with extracapsular spread, strap muscle, recurrent laryngeal nerve, and tracheal invasion, as well as metastasis to lymph nodes. In rare cases, thyroid papillary cancer can metastasize to lung or bone [2] , [3] . The presence of local or distant metastases affects tumor recurrence, patient survival rates, and quality of life, thereby leading to poor prognoses [4] .…”
Section: Introductionmentioning
confidence: 99%